2008
DOI: 10.1007/s00228-007-0447-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction between oral atorvastatin and verapamil in healthy subjects: effects of atorvastatin on the pharmacokinetics of verapamil and norverapamil

Abstract: The above data suggest that atorvastatin could inhibit the absorption of verapamil via inhibition of P-gp and/or the metabolism of verapamil by CYP3A4 in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
1
36
0
1
Order By: Relevance
“…Though this is a potential limitation, atorvastatin is not expected to meaningfully alter CYP3A4-mediated doravirine PK. This is due to atorvastatin demonstrating only a weak to moderate inhibitory effect on CYP3A4 activity (16)(17)(18). Furthermore, exposure to doravirine at 200 mg was previously well tolerated in a phase 2 trial (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though this is a potential limitation, atorvastatin is not expected to meaningfully alter CYP3A4-mediated doravirine PK. This is due to atorvastatin demonstrating only a weak to moderate inhibitory effect on CYP3A4 activity (16)(17)(18). Furthermore, exposure to doravirine at 200 mg was previously well tolerated in a phase 2 trial (2).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of modulation induced by atorvastatin was demonstrated using the 4␤-hydroxycholesterol/cholesterol ratio, a marker of CYP3A4 activity (16). The ratio was shown to decrease by only 13% following chronic treatment with atorvastatin at 20 mg, and these results, in addition to others obtained with drugs that are CYP3A4 substrates, indicate weak/moderate inhibition of CYP3A4 by atorvastatin (16)(17)(18). On the basis of their individual profiles, coadministration of doravirine and atorvastatin is not projected to result in clinically meaningful alterations to the PK of either drug.…”
mentioning
confidence: 80%
“…Calcium-channel blockers increase the plasma concentrations of some statins, possibly through the inhibition of CYP 3A4 and P-gp [27,28]. However, few studies have reported about the effects of HMG-CoA reductase inhibitors on the bioavailability or pharmacokinetics of antihypertensive agents [29][30][31][32]. Although a combination of nifedipine and statins have been clinically prescribed for treatment of hypertension, the pharmacokinetic interaction between a HMG-CoA reductase inhibitor and nifedipine in vivo has not been reported thus far.…”
Section: Introductionmentioning
confidence: 96%
“…Après administration par voie orale, le vérapamil est absorbé à plus de 90 % et subit un fort effet de premier passage hépatique avec une biodisponibilité de 10 à 20 %. Les 2 principales voies métaboliques sont la N-déméthylation (40 %) et la N-déalkylation (33 %) [3,18]. Les pourcentages de vérapamil et norvérapamil retrouvés dans les urines sont très faibles : respectivement 2 % et 1 % [19].…”
Section: Discussionunclassified